Accounting for data variability, a key factor in in vivo/in vitro relationships: application to the skin sensitization potency (in vivo LLNA versus in vitro DPRA) example. Issue 12 (15th April 2016) - Dimitrov, S.; Detroyer, A.; Piroird, C.; Gomes, C.; Eilstein, J.; Pauloin, T.; Kuseva, C.; Ivanova, H.; Popova, I.; Karakolev, Y.; Ringeissen, S.; Mekenyan, O.
Abstract: When searching for alternative methods to animal testing, confidently rescaling an in vitro result to the corresponding in vivo classification is still a challenging problem. Although one of the most important factors affecting good correlation is sample characteristics, they are very rarely integrated into correlation studies. Usually, in these studies, it is implicitly assumed that both compared values are error‐free numbers, which they are not. In this work, we propose a general methodology to analyze and integrate data variability and thus confidence estimation when rescaling from one test to another. The methodology is demonstrated through the case study of rescaling the in vitro Direct Peptide Reactivity Assay (DPRA) reactivity to the in vivo Local Lymph Node Assay (LLNA) skin sensitization potency classifications. In a first step, a comprehensive statistical analysis evaluating the reliability and variability of LLNA and DPRA as such was done. These results allowed us to link the concept of gray zones and confidence probability, which in turn represents a new perspective for a more precise knowledge of the classification of chemicals within their in vivo OR in vitro test. Next, the novelty and practical value of our methodology introducing variability into the threshold optimization between the in vitro AND in vivo test resides in the fact that it attributes a confidence probability to the predicted classification. The methodology, classification and screening approach presented in this study are not restricted to skin sensitization only. They could be helpful also for fate, toxicity and health hazard assessment where plenty of in vitro and in chemico assays and/or QSARs models are available. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A general methodology to analyze and integrate data variability when rescaling from one test to another is proposed. The methodology is demonstrated through the case study of rescaling in vitro DPRA reactivity to the in vivo LLNA skin sensitization potency classifications. A comprehensive statistical analysis evaluating the reliability and variability of LLNA and DPRA data a concept of grey zones around the thresholds and confidence probability have been introduced. The presented methodology is not restricted to skin sensitization only.